2018
DOI: 10.3389/fnagi.2018.00091
|View full text |Cite
|
Sign up to set email alerts
|

Two Behavioral Tests Allow a Better Correlation Between Cognitive Function and Expression of Synaptic Proteins

Abstract: The molecular substrate of age-associated cognitive decline (AACD) is still elusive. Evidence indicates that AACD is related to synaptic impairment in hippocampus, but different hippocampal regions play different roles, with the dorsal hippocampus (DH) associated to spatial learning, and the ventral hippocampus (VH) crucial for emotionality. If changes in hippocampal function contributes to AACD, this contribution may be reflected in alterations of synaptic protein levels. A commonly used approach to investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…As an example, aging decreases the energy status of cells [ 4 ] and disrupts lipid homeostasis, namely cholesterol metabolism [ 5 ]. Other alterations in the brain include increased oxidative stress [ 6 ] and inflammation [ 7 ], synaptic impairment [ 8 ], and decreased brain trophism [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…As an example, aging decreases the energy status of cells [ 4 ] and disrupts lipid homeostasis, namely cholesterol metabolism [ 5 ]. Other alterations in the brain include increased oxidative stress [ 6 ] and inflammation [ 7 ], synaptic impairment [ 8 ], and decreased brain trophism [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Synaptotagmin I (SYT1) is a synaptic vesicle protein that functions as a calcium sensor and is a main regulator of the SNARE complex. Convincing preclinical data have shown that SYT1 expression correlates with cognitive measures and neuronal function in rodents (Balietti et al 2018;Jia et al 2010;Chen et al 2013;Zhang et al 2017;Yu et al 2018). Recently, human genome-wide association studies (GWAS) have identified associated SNPs on SYT1 gene with personality traits as neuroticism (Luciano et al 2018), and with educational attainment and cognitive performance (Lee et al 2018).…”
Section: Introductionmentioning
confidence: 99%